Estudio de los materiales piedra y arena utilizados para la elaboración del hormigón en el cantón la Troncal provincia del Cañar - Amay Carchi, Oswaldo (2018)
In the province of Cañar many of the civil works are carried out using the rubble extracted directly from the rivers, this they do in an empirical way, ignoring if the works are made with standardized concretes that can withstand the Inclemency of the weather such as rain, wind, earthquake or the same structural charges. All these constructions made with an unknown standard are unsafe constructions; in turn they do not give security to the population………….